Promising derivatives of rutaecarpine with diverse pharmacological activities - Li, Deping; Huang, Ziqian; Xu, Xiaojun; Li, Yan (Frontiers in Chemistry, 2023)
Rutaecarpine (RUT) is a natural pentacyclic indolopyridoquinazolinone alkaloid firstly isolated from one of the most famous traditional Chinese herb-Evodia rutaecarpa, which is used for treating a variety of ailments, including headaches, gastrointestinal disorders, postpartum hemorrhage, amenorrhea difficult menstruation, and other diseases. Accumulating pharmacological studies showed that RUT possesses a wide range of pharmacological effects through different mechanisms. However, its poor physicochemical properties and moderate biological activities have hampered its clinical application. In this regard, the modification of RUT aiming at seeking its derivatives with better physicochemical properties and more potency has been extensively studied. These derivatives exhibit diverse pharmacological activities, including anti-inflammatory activity, antiatherogenic activity, anti-Alzheimer's disease activity, antitumor activity, and anti-fugi activity via a variety of mechanisms, such as inhibiting COX-2, AChE, PDE4B, PDE5, or Topos. To this perspective, this paper provides a comprehensive description of RUT derivatives by focusing on their diverse biological activities. This review aims to give an insightful of the biological activities of RUT derivatives and encourage further exploration of RUT.